DT270‐326, a Truncated Diphtheria Toxin, Increases Blood–Tumor Barrier Permeability by Upregulating the Expression of Caveolin‐1. (10th February 2016) - Lin, Yang; Wang, Ping; Liu, Yun‐Hui; Shang, Xiu‐Li; Chen, Liang‐Yu; Xue, Yi‐Xue
Summary: Aim: The nontoxic mutant of diphtheria toxin (DT) has been demonstrated to act as a receptor‐specific carrier protein to delivery drug into brain. Recent research showed that the truncated "receptorless" DT was still capable of being internalized into cells. This study investigated the effects and potential mechanisms of DT 270‐326, a truncated "receptorless" DT, on the permeability of the blood–tumor barrier (BTB). Methods: BTB and GECs were subjected to DT 270‐326 treatment. HRP flux assays, immunofluorescent, co‐immunoprecipitation, Western blot, CCK‐8, and Flow cytometry analysis were used to evaluate the effects of DT 270‐326 administration. Results: Our results revealed that 5 μ M of DT 270‐326 significantly increased the permeability of BTB in vitro, which reached its peak at 6 h. The permeability was reduced by pretreatment with filipinIII. DT 270‐326 co‐localized and interacted with caveolin‐1 via its caveolin‐binding motif. The mRNA and protein expression levels of caveolin‐1 were identical with the changes of BTB permeability. The upregulated expression of caveolin‐1 was associated with Src kinase‐dependent tyrosine phosphorylation of caveolin‐1, which subsequently induced phosphorylation and inactivation of the transcription factor Egr‐1. The combination of DT 270‐326 with doxorubicin significantly enhanced the loss of cell viability and apoptosis of U87 glioma cells in contrast to doxorubicin alone. Conclusions: DT 270‐326 might provide a novel strategy to increase the delivery of macromolecular therapeutic agents across the BTB.